Visualization and morphometrics of changes in cervical biotissues based on normalized spectral indices - Roslyakov, Olexandr; Yermolenko, Sergiy; Peresunko, Olexandr (Biophysical Bulletin, 2026)
Background: Modern visual diagnostics of precancerous and malignant lesions of the cervix requires increasing objectivity and accuracy through the use of physically based optical-spectral methods. Formation of quantitative spectral characteristics of structural changes in biotissue opens up new opportunities for differential assessment of the stage of pathology and construction of morpho-spectral screening scales.Objectives: To develop a method for spectral visualization and analysis of morpho-optical changes in cervical biotissue based on normalized spectral indices (NSI) using a compact optical module and to determine key quantitative indicators sensitive to the stages of the oncological process.Materials and Methods: To register spectral reflectance, a diagnostic module with a monochrome CMOS camera and a ring LED lighting system (450, 550, 630, 820 nm), supplemented with polarization filters, was used. NSI-map processing was carried out by calculating NSI-indexes and statistical parameters for 62 cervical images of patients of the main groups of pathologies with subsequent morphological verification.Results: The NSI_630/820 index was the most sensitive to changes in tissue density and vascularization, its average value increased from 1.303 in inflammation to 1.528 in the case of adenocarcinoma. The increase in asymmetry and kurtosis in the NSI_530/820 profiles in the case of the transition from CIN to carcinoma indicates the likely formation of areas with increased optical heterogeneity. A structured classification of intervals of values of the main morpho-optical characteristics was formed, reflecting their changes within the pathological process.Conclusions: The method of spectral-normalized visualization based on NSI indices allowed to quantitatively reflect morphological changes in the biotissue of the cervix. Indicators of changes in the spectral structure of the reflected optical signal, which correlate with the type of pathology, were established, and the effectiveness of the proposed approach for optical-physical differentiation of the stages of malignancy was proven.